Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS): Short-term outcome, functional changes in the future liver remnant, and tumor growth activity. Issue 4 (April 2015) - Tanaka, K.; Matsuo, K.; Murakami, T.; Kawaguchi, D.; Hiroshima, Y.; Koda, K.; Endo, I.; Ichikawa, Y.; Taguri, M.; Tanabe, M.
Abstract Background We compared clinical outcomes of associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) against those of classical 2-stage hepatectomy in treating metastatic liver disease. Methods Short-term outcomes, serial changes in volume of the future liver remnant (FLR), functional FLR volume, and tumor growth activity during the treatment period, were compared between our first 11 consecutive patients treated with ALPPS and 54 patients treated with classical 2-stage hepatectomy. Results Mortality in the ALPPS group (9%) tended to be higher than in the classical 2-stage group (2%, P = 0.341). The FLR hypertrophy ratio (FLR volume after vs. before the procedure) 1 week after the first operation in the ALPPS group (1.54 ± 0.18) exceeded that in the classical 2-stage group (1.19 ± 0.29, P = 0.005), being similar to the ratio at 3 weeks after the first procedure in the classical 2-stage group (1.40 ± 0.43). However, functional volume of the FLR in the ALPPS group 1 week after the first procedure (52.1%) tended to be smaller than that in the classical group 3 weeks after the first procedure (59.2%). Conclusions ALPPS should be used with extreme caution, giving special attention to postoperative complications and grade of functional liver regeneration.